O gênero notícia em sala de aula do 5º ano do ensino fundamental : um circuito de atividades de interação e produção escrita - Brandão, Joana D'arc Lopes (2021)
Recent studies on the teaching and learning of text production in Basic Educationdenoteafocus on writing practice as a process of constant improvement, which should prioritizerealsituations of language use (GERALDI, 2010; ANTUNES, 2014). In this direction, wehighlight this research, which, in its configuration, has the general objective: to developasetof didactic strategies for the textual production of the news genre, with methodologicalguidelines for the teacher of the 5th year of elementary school. In this scenario, the theoreticalbasis of this research consists of studies that consider writing a process of verbal interaction,such as Geraldi (2010, 2003), Antunes (2003, 2005, 2014), Marcuschi (2008), KochandElias(2012), Koch (2006), among others. With regard to the study on discursive/textual genres,Bakhtin (2011) and Marcuschi (2004) are based on a constant dialogue of significantinteractions; still in the context of the study of textual genres, the news will be addressedfromAlves Filho (2011), Nascimento (2009) and Barbosa (2001). As for the perspective of textualinteractive correction, we sought, in the studies by Serafini (2004) and Ruiz (2015), supportfor the construction of a methodology for evaluating the texts. The research in questionisofthe basic, documentary and bibliographic type and considers textual production as aguidingelement for the processing of written language. From this scenario, methodological guidelineswere proposed for portuguese-speaking teachers to approach the production of the newsgenre,which culminated in the production of a Methodological Guidance Notebook basedontheconception of writing as a process that requires reflection and textual rewrites. Webelievethat the didactic manual proposed in this work will enable Portuguese-speakingteacherstogradually and dynamically resume the news genre, outlineing the guiding activities of textualproduction in a context rich in reflexive possibilities that intersect and complement eachother.